The protection of property rights in criminal and civil proceedings: ECtHR practice - Stoianov, Mykola; Fedorov, Ihor; Volosko, Iryna; Gurtieva, Lyudmila; Pavlyshyn, Andriy (Amazonia Investiga, 2023)
The article is relevant in modern conditions since the protection of property rights is one of the main prerequisites for the functioning of the market economy and ensuring the country's economic development. In this regard, it is important to study the practice of the European Court of Human Rights (ECtHR) on the violation of property rights in criminal and civil proceedings, as this can help to improve the legal practice of domestic courts and ensure more effective protection of property rights. The study of the practice of the ECtHR on this topic is an important step for improving the country's legal system and ensuring proper protection of property rights, which is important for the development of society as a whole. The purpose of the research is to study the practice of the European Court of Human Rights (ECtHR) regarding the violation of the right to property in criminal and civil proceedings, as well as the analysis of this practice in order to determine the standards used by the ECtHR when considering cases related to the right to property. The methodological basis of the work consists of general scientific and special methods: the method of analyzing scientific literature, comparative analysis, empirical research methods, system analysis, and legal expertise. The result of the work is research and analysis of the practice of property rights protection in criminal and civil proceedings in accordance with international standards, which will allow to propose possible solutions for improving national practice and legislation in this area.